Can Cryptocurrencies Help Investors Diversify and Hedge the Risks of Traditional Risky Investments? An Empirical Study of Evidence from the UK - Mukherjee, Prateik (2020)
Cryptocurrencies, popularly for their underlying technology and exponential growth in numbers, also highly publicised and criticised for the booms and busts in prices and contrary stability during periods of financial turmoil, have been the subject of much speculation for investors and academics alike. This paper investigates the lack of correlation observed between the top 10 Cryptocurrencies (in terms of market capitalisation) and traditional investments, and the volatility co-movements among the Cryptocurrencies, to judge whether Cryptocurrencies can be looked at as a means of diversification and possible hedge for investors in traditional securities, like the FTSE All-Share Index, especially in periods of financial turmoil, resulting from the Chinese market crash (2015-16), the first Brexit referendum (June-2016) and the ongoing COVID-19 pandemic. Using ARIMA models for returns forecasting, and GARCH models for volatility estimation and forecasting, this paper finds Cryptocurrencies to be highly volatile and risky investments but provide weak diversification and hedging capabilities, especially given the presence of inverse leverage effects compared to the FTSE All-Share Index. From the analysis of rolling volatility forecasts, 5% VaR estimations, and the performance of bivariate global minimum variance portfolios, this paper also finds risk-averse investors to face higher odds of loss at the 5% quantiles but the inverse leverage effects provides risk-loving investors chances to increase their risk-rewards from longer term Cryptocurrency investments. Moreover, the optimal portfolios suggest a weak positive correlation between each Cryptocurrency and the FTSE All-Share Index, apart from Tether (USDT), which seems to display qualities of a riskless asset and providing the strongest diversification option for investors, especially during the COVID-19 pandemic.